Millennials’ Behavioural Intention of Sharing Online Video Advertising (OVAs): Mediating Role of Company Reputation Perspective - Ismail, An Nur Nabila; Zainordin, Nik Mohamad Shamim Nik Mohd; Omar, Wan Marhaini Wan; Zulqernain, Nurul Syaqirah (Advances in Social Sciences Research Journal, 2024)
Online Video Advertisings (OVAs) have become more popular due to the increasing number of people who use the internet to search for information and buy things. This study examines three components of Theory Planned Behaviour (TPB): attitude (ATT), subjective norm (SN), and perceived behavioural control (PBC), and how they relate to sharing OVAs. The study investigates how company reputation impacts the correlation between these variables. A total of 208 millennials in Selangor were given questionnaire to gather the data. Partial least squares-structural equation modelling technique was used to examine the data. The findings show that ATT and SN have an impact on millennials’ intention to share OVA. The mediation result indicates that company reputation partially mediates the relationship between PBC and the intention to share OVAs. The results of this study add to the body of knowledge while giving practitioners, particularly marketers, practical knowledge about efficient marketing strategies.